Acceleration of community-based tourism village development in West Java Province - Juliana Juliana; Diena M Lemy; Ira B Hubner; Rudy Pramono; Sandra Maleachi; Nova Bernedeta Sitorus (Jurnal Pariwisata Pesona, 2022)
The purpose of this study was to identify the potential of community-based village tourism in West Java. The type of research used is descriptive qualitative method. The informants in this study were tourism stakeholders in West Java Province, which were determined by purposive technique with a total of 9 people. The results showed that West Java Province has tourism villages with nature-based tourist attractions in the form of lakes, waterfalls and mountains with unique views, cultural tourism attractions in the form of cultural heritage where there are caves with historical relics, as well as museums that are rich in original collections. The government has a strong desire to develop original and nature-based tourist attractions. Utilization of social media and organizing events are used as a means of tourism promotion. Acceleration in the development of community-based tourism villages in West Java Province is  collaboration from stakeholders,  requires support from the government and awareness of village communities in management requires support for rural communities for development and efforts for promotion.